The Impact of the Liberalization of the Exchange Rate in Egypt in 2016 on the Inflation Rate in the Short Term - Abd El Ghany, Sanaa Mohamed (The Arab Journal of Administration, 2025)
The main objective of the research was embodied in studying the impact of exchange rate liberalization on the inflation rate in Egypt. The research concluded that there is a relationship between the exchange rate systems and inflation rates, and there is a strong direct relationship between the exchange rate and the inflation rate, and quantitative indicators confirmed that enable the Egyptian state to control The exchange rate of the dollar, as a result of the comprehensive economic reform program that it produced, which preserved the value of the Egyptian pound in the past three years, and that there are some negative effects on the Egyptian economy represented by the high rate of inflation, which made the economy lose part of its competitiveness. The research recommended emphasizing the makers of economic policies to exercise caution and caution when following the flexible exchange policy in accordance with the economic conditions because of the economic and social effects of that decisions, and that the relationship between monetary policy tools and the inflation rate be stable with what can be predicted, and the monetary authority must have The ability to influence its various tools effectively and efficiently in the event of a deviation in the inflation rate from its value in the future, and the necessity of having developed financial markets for capital for the optimal use of these tools so that their impact on economic activity is transmitted to enable the correction process in a timely manner.